OPTIMASI PRODUKSI LAPANGAN X DENGAN MENGGUNAKAN TEKNIK SURFACTANT FLOODING PADA POLA INJEKSI FIVE SPOT - Zaky Faisal, Mochamad
Surfactant flooding is one of the well stimulation technique that can be applied in mature field to increases the oil recovery factor. This technique has same principle with water flooding, injecting fluid to the reservoir to push oil into production well. The difference is the composition of fluid injection. Water flooding only use water as an injected fluid. Meanwhile, surfactant flooding using surfactant as an extra component to be mix with water as an injected fluid for the injection process to the reservoir. If water flooding only use water energy to push the oil into production well, surfactant component on the surfactant flooding reduce interfacial tension as well. The advantages of using surfactant flooding is reduce the interfacial tension between oil and water. Beside that, surfactant ability to change rock wettability can improve oil production. Surfactant flooding parameter like injection rate and surfactant concentration must be optimize to gain maximum cumulative oil production.